An Echocardiographic Study of Right Ventricular Morphology and Function in Systemic Hypertension. - Barakoti, Murari Prasad; Karki, Adhyashree; Chaulagain, Manoj Kumar; Karki, D B (Nepalese Heart Journal, 2021)
Background and Aims: Hypertension is a common medical condition that leads to increased risk of cardiovascular conditions including coronary artery disease, heart failure, stroke, renal diseases, blindness and cardiovascular death. Long term hypertension will affect left ventricle by hypertrophy and several functional derangements. Since heart works as a unit, right heart changes are expected. Right ventricular dysfunction has a strong prognostic significance and we aim to study right ventricular parameters in hypertensive patients.Methods: We studied 71 hypertensive subjects and 66 matched control without hypertension in echocardiography laboratory for chamber dimensions and right ventricular systolic and diastolic parameters.Results: The right ventricular free wall thickness (5.46±1.97mm vs 4.77±0.81mm; P=0.01) and interventricular septal thickness (11.62±2.64mm vs 9.10±1.16mm; P